Anogenital HIV RNA in Thai men who have sex with men in Bangkok during acute HIV infection and after randomization to standard vs. intensified antiretroviral regimens. Issue 1 (7th May 2015) - Phanuphak, Nittaya; Teeratakulpisarn, Nipat; van Griensven, Frits; Chomchey, Nitiya; Pinyakorn, Suteeraporn; Fletcher, James LK; Trichavaroj, Rapee; Pattanachaiwit, Supanit; Michael, Nelson; Phanuphak, Praphan; Kim, Jerome H; Ananworanich, Jintanat; et al.
Abstract : Introduction: HIV transmission risk is highest during acute HIV infection (AHI). We evaluated HIV RNA in the anogenital compartment in men who have sex with men (MSM) during AHI and compared time to undetectable HIV RNA after three‐drug versus five‐drug antiretroviral therapy (ART) to understand risk for onward HIV transmission. Methods: MSM with AHI ( n= 54) had blood, seminal plasma and anal lavage collected for HIV RNA at baseline, days 3 and 7, and weeks 2, 4, 12 and 24. Data were compared between AHI stages: 1 (fourth‐generation antigen‐antibody combo immunoassay [IA]–, third‐generation IA–, n= 15), 2 (fourth‐generation IA+, third‐generation IA–, n= 9) and 3 (fourth‐generation IA+, third‐generation IA+, western blot–/indeterminate, n= 30) by randomization to five‐drug (tenofovir+emtricitabine+efavirenz+raltegravir+maraviroc, n= 18) versus three‐drug (tenofovir+emtricitabine+efavirenz, n= 18) regimens. Results: Mean age was 29 years and mean duration since HIV exposure was 15.4 days. Mean baseline HIV RNA was 5.5 in blood, 3.9 in seminal plasma and 2.6 log10 copies/ml in anal lavage ( p <0.001). Blood and seminal plasma HIV RNA were higher in AHI Stage 3 compared to Stage 1 ( p <0.01). Median time from ART initiation to HIV RNA <50 copies/ml was 60 days in blood, 15 days in seminal plasma and three days in anal lavage. Compared with the three‐drug ART, the five‐drug ART had a shorter time to HIV RNA <1500 copies/ml in blood (15 vs. 29 days, p= 0.005) and <50 copies/ml in seminal plasma (13 vs. 24 days, p= 0.048). Conclusions: Among MSM with AHI, HIV RNA was highest in blood, followed by seminal plasma and anal lavage. ART rapidly reduced HIV RNA in all compartments, with regimen intensified by raltegravir and maraviroc showing faster HIV RNA reductions in blood and seminal plasma.